Towards Indonesia’s 2024: A Multimodal Analysis of Presidential Election Online Posters - Meliana Siboro; T. Silvana Sinar (LingPoet: Journal of Linguistics and Literary Research, 2023)
This study focuses on online posters about 2024 presidential election of Indonesia. The aim of this study is to analyze online political posters made for the campaigns of the elections. Four online posters of presidential candidates for the 2024 election have been chosen randomly. The visual devices are analyzed using Kress and van Leeuwen’s (2006) model and political discourse analysis is used to determine the primary discursive methods that are utilized in the effort to sway the voting behavior of the American populace in a particular direction. The results show that the posters share some characteristics while distinguishing themselves in other others. These devices are reflection of the respective parties or candidates’ ideologies. Quotation, repetition, uplifting language, and concise phrases are some of the defining characteristics of the written texts that appear on the election posters. The phrases and sentences have been selected as well as the wording for the purpose of making them more effective.